Amorphous materials for elementary-gas-involved electrocatalysis: an overview. Issue 47 (30th November 2021) - Zhai, Wenfang; Sakthivel, Thangavel; Chen, Fuyi; Du, Chengfeng; Yu, Hong; Dai, Zhengfei
Abstract : The summary and perspective on fabrication, structure tuning, and elemental-gas-involved catalytic applications of amorphous materials have been outlined in this review. Abstract : Given the critical demands on energy conversion, storage, and transportation, tremendous interest has been devoted to the field of material development related to energy harvesting, recently. As the only route towards energy utilization, the carriers with the characteristics of low carbon are regarded as the future choice, e.g., hydrogen and ammonia. To this end, electrocatalysis provides a green way to access these substances. However, the unfulfilled conversion efficiency is the bottleneck for practical application. In this review, the promising characteristics of amorphous materials and the amorphous-induced electrocatalytic enhancement (AIEE) were emphasized. In the beginning, the characteristics of amorphous materials are briefly summarized. The basic mechanism of heterogeneous electrocatalytic reactions is illustrated, including the hydrogen/oxygen evolution and oxygen/nitrogen reduction. In the third part, the electrocatalytic performance of amorphous materials is discussed in detail, and the mechanism of AIEE is highlighted. In the last section of this review, the challenges and outlook for the development of amorphous enhanced electrocatalysis are presented.